ASSESSMENT OF THE INNOVATIVE MANAGEMENT PROCESS OF A BUSINESS ORGANIZATION - DANYLIUK, Viacheslav; SALII, Anhelina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes approaches to the evaluation of the process of managing the innovative activity of a business organization, and gives an example of such a process in a production-type organization. The relationship between the process of evaluating innovative activity and measuring the effectiveness of business organization activity is shown, a comparison of modern and traditional approaches to evaluating the effectiveness of business organization activity is made, and common points with the process of evaluating the management of innovative activity are identified. The characteristics of four main approaches are presented: multi-criteria, cost-based, risk-oriented, integrated. The main indicators on the basis of which it is possible to evaluate the innovative activity of an innovatively active business organization are given: indicators characterizing the innovative level of a business organization, indicators characterizing the production effect of the application of innovation, and indicators characterizing the financial efficiency of innovations. The relationship between innovation and investment is shown, the main factors affecting investment in innovation activity are identified, among them: high cost of innovation activity, creation of intellectual property, probability of success and uncertainty of the results of innovation activity, which makes it difficult to forecast the main parameters of such activity, etc. The innovative activity of LLC "MARGIT" was studied: the analysis of innovative solutions of the business organization was carried out according to the main groups of innovations, a map of the potential of innovation projects of LLC "MARGIT" was built. The strategic assets of the business organization, on the basis of which a new innovation process can be initiated and implemented, have been analyzed. Within such an analysis, the most important functional areas for a business organization are delineated, namely: finance, technology, fixed assets, research and development, marketing, etc.
Keywords: management; innovative activity; assessment; innovative potential; business organization